(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: Dispute resolution is the process through which conflicts, misunderstandings are handled. It is an effective process for smooth functioning of any sort of organization. It further helps in maintain peace in the society as well as organization. Objective: This study seeks to appraise and evaluate the effectiveness of Dispute Resolution Councils (DRCs) in the select districts of Khyber Pakhtunkhwa, Pakistan. Methods: The effectiveness of ADR forums is gauged through magnitude of satisfaction and trust of beneficiaries accessing its services as well as affordability and timeliness of dispensation of justice to them. Findings: It was found that DRCs have become highly consequential to the peacemaking due to impartial setup and the provision of equal opportunity to parties involved in any case. Conclusion: Despite the overall success of DRCs, they are still affected by problems such a poor documentation, infrastructure, lack of training and most importantly the absence of any enforcement mechanism of their decisions. Implication: This study puts forth various reforms that may include the standardization of documents, provision of sufficient capital and adequate infrastructure, and auguring the role of these avenues to strengthen the implementation of their decisions.